La representación de documentos y autoridades archivísticas: Una mirada desde la perspectiva de la normalización - Padrón, Dunia Llanes [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (FapUNIFESP (SciELO), 2017)
Nowadays, the archival science is going through a big changes in its conception as science. As a result, the discipline has gone from the inactivity in the normalization of their tasks to the regulatory action of most its processes. In the late twentieth century, institutions such as the International Council on Archives and prestigious associations of archivists began to develop standards to simplify working methods and ensure better results in the representation and information retrieval processes. This paper aims to identify, describe and categorize the general and internal structure of descriptive standards published after ISAD(G) and ISAAR(CPF) which constitute models for representing documents and authorities. This research is mainly of a descriptive nature and focuses on the study of international, national and regional standards published about the archival entities representation. Actually, you can access to the information from multiple perspectives and the collaborative work among information institutions, it is impossible to execute archival processes that are not standardized. The use of canons to represent information certifies the reliability, consistency, accessibility, availability and appropriation of any information source and interoperability between systems of any institution.
The representation the documents and authorities archivist: A look from the perspective of standardization
Keywords: Representation and retrieve information; Standardization; Standards description